Systemic Digital Marketing Management for MSMEs in Central Java through ISM and MULTIPOL Strategic Analysis - Desi Trisnawati; Rosana Eri Puspita; Anwar M Radiamoda (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Central Java continue to face challenges in managing digital marketing, particularly in terms of technological capability, access to funding, and market competitiveness. Although digital platforms provide broader market opportunities, many MSMEs still struggle to implement digital marketing strategically and sustainably. This study aims to identify the key drivers of digital marketing management among MSMEs and examine the structural relationships among these drivers within a systemic framework. The study employed a qualitative approach using Soft Systems Methodology (SSM) with CATWOE analysis and prospective analysis through the MULTIPOL method. Data were collected through focus group discussions involving stakeholders from the MSME digital marketing ecosystem in Central Java. The findings reveal that national and municipal regulations, funding support, technical IT support, product quality, and product diversification are the main factors influencing digital marketing performance. In addition, education-based strategies, digital marketing training, and product development were identified as the most influential strategic actions in strengthening MSME competitiveness. The study concludes that effective digital marketing management requires integrating institutional support, digital capability development, and market-oriented product strategies. These findings provide practical insights for policymakers and MSME actors in designing more adaptive and sustainable digital marketing strategies.